ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGY ON THE BANKING SECTOR (A STUDY WITH SPECIAL REFERENCE TO BANKS IN TIRUNELVELI DIST.) (International Journal of Food and Nutritional Sciences, 2022)
A bank is a financial institution that provides customers. A bank is generally understood as an institution which provides fundamental banking services such as accepting deposits and providing loans. There also non-banking Institutions that provides certain banking services without meeting the legal definition of a bank. Banks are a subset of the financial services industry. Today, Information Communication Technology has become the heart of banking sector, while banking industry is the heart of every rebuts economy. The ICT development has a significant effect on development of more flexible and users friendly banking services. ICT has created a new infrastructure for the world economy to become truly global and also provided the users of new technology a competitive advantage over their rivals. Electronic banking system has become the main technology driver revolution in conducting financial transactions. However, banks have made huge investments in telecommunication and electronic systems users have also been validated to accept electronic banking system as useful and easy to use.